Assessing Australia’s Progress Towards a National Broadband Strategy at December 2021 - TelSoc Broadband Futures Group, . (Journal of Telecommunications and the Digital Economy, 2021)
This paper is based on a report by the TelSoc Broadband Futures Group in which Australia’s progress during 2021 towards a National Broadband Strategy is assessed against the criteria set out in Towards a National Broadband Strategy for Australia: 2020-2030, a report prepared by TelSoc in November 2020. The Journal publishes this assessment of progress as a Special Interest Paper. The Assessment shows that there has been some, albeit limited, progress towards a National Broadband Strategy, including in various Australian Government statements about the development of the digital economy and its expectations of NBN Co in the provision of fixed broadband access services nationally.